PHYSYCHOCHEMICAL CHARACTERISTICS OF GELATIN BONE OF FISH (Congresox talabon) WITH SOAKING ACID - Anggito Naibaho; Rahman Karnila; Mirna Ilza (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
AbstractThis study aims to determine the physicochemical characteristics of cunang fish bone gelatin(Congresox talabon) with immersion in weak acids (phosphate, citrate, acetate) in theprocess demineralization of cunang fish bones. Physical parameter analysis includes (yield, viscosity, pH), and chemical parameters include (moisture content, ash content, protein content). This research method is an experimental method using a non-factorial Completely Randomized Design (CRD) with 3 treatments: G1 (phosphoric acid immersion), G2 (citric acid immersion), G3 (acetic acid immersion) and the data were processed using analysis of variance (ANOVA). The results of the research on the characteristics of cunang fish bone gelatin obtained were G1 was the best treatment with a yield value of 8.89% and the analysis results had met the standards including viscosity, pH, moisture content, ash content, protein content, namely 4.00 cPs, 4.46, 6 , 39%, 11.76% and 54.74%.Keywords: citric acid, acetic acid, phosphoric acid, Congresox talabon, Gelatin